C-reactive protein – My perspective on its first half century, 1930-1982 - Kushner, Irving (Frontiers in Immunology, 2023)
C-reactive protein (CRP) was discovered in 1930 in the sera of patients during the acute phase of pneumococcal pneumonia and was so named because it bound to the C-polysaccharide of the pneumococcal cell wall. During the next half century many questions raise by this discovery were answered. Phosphorylcholine was found to be the moiety of the C-polysaccharide to which CRP bound. The molecular structure of CRP was elucidated: five identical subunits arranged in cyclic symmetry, giving rise to the term pentraxin. Initially felt to be not normally present in the blood, CRP was found to be a component of normal serum in trace amounts. Its site of origin was determined to be the hepatocyte. It became clear that the presumed humoral mediator responsible for CRP induction was of leukocytic origin. Binding of CRP to its ligand activated the complement system, one of the important effector mechanisms of innate immunity. CRP was found to stimulate phagocytosis of some bacterial species via binding to Fc receptors and was found to be protective in vivo against the pneumococcus in mice. It appeared likely that a related function of CRP was clearance of necrotic tissue. CRP was recognized as being a highly evolutionary conserved molecule. Its discovery during the acute phase of pneumococcal pneumonia led to its being dubbed an acute phase protein. What we today call “the acute phase response”, refers to the large number of behavioral, physiologic, biochemical, and nutritional changes that occur during inflammatory states.